RELATIONSHIP BETWEEN DURATION OF BOTTLE FEEDING AND OCCLUSION IN PRIMARY DENTITION - Ika Anisyah; Retno Hayati; Margaretha Suharsini (Faculty of Dentistry, Universitas Indonesia, 2015)
Bottle-feeding period more than one year may influence the occlusion and will disturb the formation of strong muscle jaw. This effect will give an adverse result to permanent teeth. The type of malocclusion resulted from bad oral habit, may vary, depends on the type of oral habit, intensity, duration and frequency. The purpose of this study was to observe the relationship between duration of bottle-feeding and occlusion of primary teeth. The following occlusion relationships examined were overbite, overjet, canine relationship, and terminal plane. The design of this was cross-sectional analytic, which was carried out in pre-school children aged between 3-5 years old. The duration of bottle-feeding was categorized in 24 months, 25-36 months, 37-48 months, and >48 months. Overbite and overjet were measured from the cast using a digital caliper. Canine relationship and terminal plane were also measured from the cast. The result of Pearson Correlation test revealed a weak relationship between the period of bottle-feeding and overbite (0,329) and overjet (r=0,372), whereas the result of Chi-Square test, used to investigate the correlation between canine (r=0,111) and terminal plane was not statistically significant (r=0,170). Anova test was carried out to observe the difference of overbite and overjet affected by duration of bottle-feeding. The result demonstrated an increase of overbite and overjet if duration of bottle-feeding was prolonged. Tukey HSD test result on bottle-feeding duration and overbite shows significant differences between group of ≤ 24 months, 25-36 months, and group of 37-48 months. Meanwhile Tukey HSD test result on bottle-feeding duration on overjet shows significant differences between group of ≤ 24 months, group of 37-48 months, and >48 months duration.